443. West Nile Virus in Humans in Greece, 2010–2017. (26th November 2018) - Pervanidou, Danai; Vakali, Annita; Baka, Agoritsa; Georgakopoulou, Theano; Danis, Kostas; Detsis, Marios; Tsakris, Athanasios; Papa, Anna; Tsiodras, Sotirios; Panagiotopoulos, Takis; Hadjichristodoulou, Christos
Abstract: Background: In 2010, the first West Nile (WN) virus outbreak was recorded in Central Macedonia, northern Greece, with 197 WN neuroinvasive disease (WNND) cases; the largest reported in Europe since 1996. In the consecutive years, seasonal outbreaks continued to occur. We investigated the 2010–2017 outbreaks to determine their extent, describe the geographical and temporal distribution of human cases and implement appropriate control measures. Methods: We supported the investigation of suspected human cases and strengthened the laboratory surveillance. We interviewed cases and treating physicians and recorded suspected place of exposure, type of disease (WNND or non-WNND) and disease outcome. We estimated case fatality (CF) of neuro-invasive disease (WNND). PCR-positive samples were sequenced. Results: Since 2010, a total of 672 human cases were recorded, from June to October, including 474 (71%) WNND cases. Cases were recorded for five consecutive years, in 2010 ( n = 262), 2011 ( n = 100), 2012 ( n = 161), 2013 ( n = 86), and 2014 ( n = 15); and then in 2017 ( n = 48), after a 2-year period with no cases diagnosed. Since 2010, a total of 81 (CF=17%) fatalities occurred among WNND cases, with a median age of 80 (49–95) years. Cases were recorded, in both urban and rural areas, in half (37/74) of the Regional Units (NUT-3 level), in all 13 Regions. In 2011, the virus dispersed southwards to newly affected Regional Units, and in the following years cases were recorded both in previously affected and in new areas, during each transmission season. In 2017, cases were also recorded for the first time in the two last—previously non-affected—Regions of the country. Sequences from PCR-positive samples revealed WNV lineage 2, with high genetic similarity to the 2010 strain. Conclusion: The reoccurrence of human cases and the spread of the virus in newly affected areas suggests that WNV lineage 2 has been established in Greece; its circulation and occurrence of cases remain likely in the following transmission periods, in previously affected and in new areas. Enhanced surveillance throughout Greece is critical to timely implement targeted control and prevention measures (i.e., communication campaigns, vector control, and blood safety measures). Disclosures: All authors: No reported disclosures.